THE DYNAMICS OF WAQF ASSET MANAGEMENT IN INDONESIA - Rozihan Rozihan (UNISSULA, 2022)
The aims of this study was to determine the effectiveness of waqf management after the enactment of the waqf management law in Indonesia. As we all know that waqf is not only normative worship but also has a social element in it, thus making it one of the keys to the welfare of Muslims. Therefore, the management of waqf property is very important to be known together. This research used normative juridical research that examines the legal provisions of waqf property management in Indonesia and the study of legal instruments in classical fiqh books regarding waqf management. The potential of waqf in Indonesia is very large, for that the Indonesian government must establish a regulation that regulates the procedures for the collection and management of waqf assets as regulated in Act No. 41 of 2004 concerning waqf. The regulation had led to the birth of an independent institution in charge of collecting and managing waqf assets which are called the Indonesian Waqf Board (BWI). Therefore, there is a need for synergy from various parties regarding the collection and management of waqf assets. If so far BWI is an independent institution in charge of managing waqf, so it is necessary to coordinate with the Agrarian Office, waqf asset management institutions operating in the private sector such as the Indonesian Waqf Savings Account or non-governmental organizations (NGOs). This is done with the hope that Indonesia can optimize its waqf assets and the result of waqf can become an instrument that can reduce poverty.